The Strategy to form of Customer Opinion for the Eternal Stuff through Social Media - Fairuz Satria Ananda, Muhammad; Damayanti, Trie; Yanti Setianti, Dan (International Journal of Psychosocial Rehabilitation, 2019)
Eternal stuff is a new company engaged in stationery. As a new company engaged in business that already has many competitors external stuff needs to form a customer opinion on the new brand. Eternal stuff uses marketing public relations efforts that function to create markets, maintain product image and establish relationships with customers. Based on this, the purpose of this study is: to find out the planning and implementation of the marketing strategy of the Public Relations Eternal Stuff in using social media as an effort to form a Customer opinion on the Eternal Stuff brand. The results show that the first step taken by Eternal Stuff is to create an Instagram account and actively follow those who are considered to be the target market for the Eternal Stuff. The conclusion obtained is that efforts to form customer opinions through social media can be done by choosing social media tailored to the target product targets. Because stationery products have targeted Instagram and LINE students and students as the main media to be important, because opinions will be formed if the exposure of the product can reach its target, while social media is a tool that can easily measure the extent to which the customer believes in the product, and if the opinion has been formed, the image of the brand will be easily formed so that the market will be formed.